An in vivo confocal microscopy study of corneal changes in pseudoexfoliation syndrome. Issue 5 (September 2019) - Terracciano, Luca; Cennamo, Michela; Favuzza, Eleonora; Julia, Litasova; Caporossi, Orsola; Mencucci, Rita
Purpose: To evaluate, through the in vivo confocal microscopy, the pathological changes of each corneal layer in eyes affected by pseudoexfoliation syndrome. Methods: We studied 40 eyes of 40 patients with diagnosis of unilateral senile cataract associated with pseudoexfoliation syndrome and 40 eyes of 40 control subjects with senile cataract without pseudoexfoliation syndrome. All patients underwent a complete ophthalmic examination including best corrected visual acuity, slit-lamp examination, corneal sensitivity measurement using a Cochet-Bonnet nylon thread esthesiometer, and anterior segment optical coherence tomography (Visante OCT, Carl Zeiss Meditec AG, Germany); in vivo confocal microscopy of corneal sections (endothelium, stroma, sub-basal nerve plexus, and superficial and basal epithelium) was performed with the ConfoScan 4.0 (Nidek, Japan). Results: In pseudoexfoliation syndrome group, the mean corneal sensitivity was 44.1 ± 1.3 mm and in the control group was 55.6 ± 4.7 mm. The corneas of the eyes with pseudoexfoliation syndrome were significantly less sensitive than those of control group eyes (p < 0.001). Pseudoexfoliation syndrome eyes had a lower nerve density and less nerve beadings and a higher degree of tortuosity in sub-basal plexus compared to the control group. The cell density of epithelial and endothelial layers was significantly lower in pseudoexfoliation syndrome eyes than controls. In 80% of pseudoexfoliation syndrome eyes, we found activated keratocytes and inflammatory cells in the anterior stroma. Conclusion: Our study demonstrates the morpho-structural corneal alterations in eyes affected by pseudoexfoliation syndrome, using corneal in vivo confocal microscopy as a non-invasive and high-reproducible technique to evaluate pathophysiology of each corneal layer; the sub-basal nerve plexus alterations are correlated with the lower corneal sensitivity.